Urgensi Penetapan Air Defense Identification Zone Pada Kawasan Regional - Astuti Astuti; Josina Augustina Yvonne Wattimena; Irma Halimah Hanafi (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: Air Defense Identification Zone (ADIZ) is a zone for identification purposes in the air defense system for a country, which according to international custom generally extends from the territorial area of a country to reach the air space above the free sea bordering the country.Purposes of the Research: to find out the setting of the Air Defense Identification Zone and what is the urgency of establishing the Air Defense Identification Zone in the regional area. The method used in writing this thesis is a normative research method. The legal materials used are primary, secondary and tertiary legal materials.Methods of the Research:  This legal research, the author uses normative research. That is, a study that primarily examines positive legal provisions, legal principles, and legal doctrines to answer legal questions faced. Results of the Research: The results obtained are that the regulation of the Air Defense Identification Zone (ADIZ) according to international law is, based on the provisions of the 1944 Chicago Convention, customary international law and also Article 51 of the United Nations Charter, furthermore with the stipulation of ADIZ in a regional area can be considered a defensive step. to provide advance notice of potential threats and efforts to improve flight safety in the region and provide benefits to national and international aviation safety.